The effect of internal and external focus of attention on tennis skill acquisition in children - Tapan, Tuncay; Şahan, Asuman; Erman, Kemal Alparslan (Frontiers in Psychology, 2023)
The aim of this study was to examine the effect of internal and external focus attention instructions on learning tennis groundstroke (forehand-backhand drive) for children. Methods: A total of 60 (30 girls, 30 boys) children aged 10.24 ± 0.48 years were included in the study. Children were randomly divided into three groups External Focused Group (EFG), Internal Focused Group (IFG) and Control Group (CG). Results: In the pre-training tests of Tennis Skill (TST) and Tennis Transfer (TTT), there was no significant difference between the three groups (EFG, IFG and CG) according to one-way ANOVA results (p > 0.05). Significant interaction was determined between groups and measurements in a repeated-measures ANOVA analysis (three groups, three measurements) and TST and TTT (p < 0.01). According to the post-hoc analysis, it was determined that TST results increased significantly in the EFG compared to the IFG and CG, and there was no significant difference in the TTT between EFG and IFG, but both groups showed significant improvements compared to CG. Conclusion: Instructions to children to focus attention externally facilitate learning the groundstroke (forehand-backhand) technique, which is one of the basic tennis techniques.